IMPLEMENTASI SEKOLAH SIAGA BENCANA PADA SMAN 2 RANAH PESISIR - Syam, Alexander; Arif, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2019)
SMAN 2 Pasisir is in the Red Zone position and the people there are still unfamiliar with safety in the event of an earthquake. We know that students are usually very panicked when there is an earthquake, but there is no knowledge given either from parents or teachers to children or students. For the need for the Implementation of Disaster Preparedness Schools in SMAN 2 Ranah Pesisir. The purpose of this study is to look at the implementation of a disaster preparedness school in the in SMAN 2 Ranah Pesisir, where the importance of students is to know a disaster preparedness school. Whereas in SMAN 2 Ranah Pesisir is very potential for earthquake and tsunami disasters because it is in the tsunami hazard zone, Coastal Area Public High School is in a radius of 1-2 KM if pulled straight from the shoreline. If there is a tsunami potential to be affected is very large because based on the condition of the school located in a very wide plain without any barrier waves such as buildings and buildings. The students 'knowledge about earthquake and tsunami mitigation as a whole is in the good category while the students' knowledge about the earthquake and tsunami disasters is in the sufficient category, this can be seen from the large frequency and percentage in the table above. Based on the evacuation path to TEA from in SMAN 2 Ranah Pesisir, students only ran straight towards TEA as far as 500 meters towards the hill. The tsunami evacuation route in in SMAN 2 Ranah Pesisir is still classified as inappropriate but the evacuation network has no barrier or obstruction to TEA. In addition, the distance from the settlement to the evacuation route and continued to the final evacuation site is sufficient, because the final tsunami evacuation site for people walking is approximately 30 minutes